2001
DOI: 10.1097/00001648-200101000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Flavonols and Flavones and Risk of Coronary Heart Disease in Male Smokers

Abstract: Flavonols and flavones are antioxidant polyphenolic compounds found in tea, vegetables, fruits, and wine. In experimental studies they have been effective free radical scavengers, metal chelators, and antithrombotic agents. In the few epidemiologic studies of these agents, some have suggested an inverse association between intake of flavonols and flavones and the risk of cardiovascular disease. Our study population comprised 25,372 male smokers, 50-69 years of age, with no previous myocardial infarction. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 20 publications
6
94
3
4
Order By: Relevance
“…Moreover, the bioavailability of flavonols from tea has been shown to be only about 50% of that from other sources such as onions (Hollman & Katan, 1999) suggesting that flavonol intake from tea may not be as beneficial as that derived from fruits, vegetables and red wine. In support of this, subgroup analyses of specific sources of flavonols with CHD mortality indicated that tea consumption was unrelated to CHD risk after adjustment for dietary factors Yochum et al, 1999) , whereas high intakes of flavonols from vegetable sources, such as broccoli and onions, were significantly and inversely associated with CHD mortality Yochum et al, 1999;Hirvonen et al, 2001). …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, the bioavailability of flavonols from tea has been shown to be only about 50% of that from other sources such as onions (Hollman & Katan, 1999) suggesting that flavonol intake from tea may not be as beneficial as that derived from fruits, vegetables and red wine. In support of this, subgroup analyses of specific sources of flavonols with CHD mortality indicated that tea consumption was unrelated to CHD risk after adjustment for dietary factors Yochum et al, 1999) , whereas high intakes of flavonols from vegetable sources, such as broccoli and onions, were significantly and inversely associated with CHD mortality Yochum et al, 1999;Hirvonen et al, 2001). …”
Section: Discussionmentioning
confidence: 85%
“…Excluding this study from the pooled estimate had little impact on the overall effect size (RR ¼ 0.77, 95% CI 0.66-0.90). Additional sensitivity analyses indicated that the point estimate and CI for the risk reduction were not significantly altered with the exclusion of any individual study although the reduction of risk to 0.74 (95% CI 0.63-0.87) with the exclusion of the study by Hirvonen et al (2001) suggests that this cohort, which had the largest number of events, was the most influential.…”
Section: Resultsmentioning
confidence: 94%
“…However, flavonoids exhibit various effects on mammalian cells with interesting implications for inflammation [133], cardiovascular disease [81,83] and cancer [58] involving the modulation of redox functions, calcium homeostasis [227], the activity of various enzyme systems, proliferation and differentiation, and the response to a variety of stimuli (reviewed in [134]). The effects of flavonoids are often pictured as beneficial for cell survival, preventive against oxidative insults and anti-carcinogenic.…”
Section: Biological and Cellular Propertiesmentioning
confidence: 99%
“…Both experimental and epidemiological evidence support a role of polyphenols in the prevention chronic diseases and more particularly cardiovascular diseases and cancers . Polyphenol intake has been related to disease in epidemiological studies, and especially inverse associations with cardiovascular risk have been observed (Hertog et al, 1993;Knekt et al, 1996;Hirvonen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%